The Development of Health Psychology from the Construction of Public Health in Brazil - Sobrosa, Gênesis Marimar Rodrigues; Zappe, Jana Gonçalves; Patias, Naiana Dapieve; Fiorin, Pascale Chechi; Dias, Ana Cristina Garcia (Revista de Psicologia da IMED, 2014)
This paper presents a brief discussion about the Brazilian Public Health and the introduction of Health Psychology in the Unified Health System considering publications about these topics. At first, the History of Public Health is briefly presented, in order to understand the development of Health Psychology and how psychologists started working with health-disease contexts in this field. Then, Health Psychology area is presented and its limits and perspectives are considered. It has been concluded that psychologists, especially those who work with Public Health, need to review their practices, because they are still focused on disease and do not take into consideration the history and context of health-disease processes.